Effects of heart rate reduction with ivabradine on vascular stiffness and endothelial function in chronic stable coronary artery disease. Issue 5 (May 2019) - Hohneck, Anna Lena; Fries, Peter; Ströder, Jonas; Schneider, Günther; Wagenpfeil, Stefan; Schirmer, Stephan Henrik; Böhm, Michael; Laufs, Ulrich; Custodis, Florian
Abstract : Introduction: Epidemiological and clinical studies have shown a relevant association between heart rate and cardiovascular mortality. Experimental studies identified vascular effects of heart rate reduction with the I f channel inhibitor ivabradine. Therefore, the effects of heart rate reduction on endothelial function and indices of arterial stiffness were examined in patients with stable coronary artery disease in a prospective, placebo-controlled clinical crossover study. Methods and results: Twenty-three patients (18 men and 5 women) with a resting heart rate (HR) of at least 70 beats per minute (bpm) and stable coronary artery disease were enrolled in this study. In a cross-over design, all patients were treated with ivabradine (Iva, 7.5 mg b.i.d.) and placebo for 6 months each. Iva reduced heart rate by 11.4 bpm (Iva 58.8 ± 8.2 bpm vs. placebo 70.2 ± 8.3 bpm, P < 0.0001). Augmentation index (AIx75), carotid–femoral pulse wave velocity (cfPWV) and central aortic blood pressure were measured using applanation tonometry (SphygmoCor). HRR by Iva increased AIx75 by 12.4% (Iva 24.3 ± 10.5% vs. placebo 21.3 ± 10.1%, P < 0.05) and reduced cfPWV by 14.1% (Iva 6.3 ± 1.7 m/s vs. placebo 7.3 ± 1.4 m/s, P < 0.01). Iva increased mean central blood pressure by 7.8% (Iva 107.5 ± 15.4 mmHg vs. placebo 99.1 ± 12.2 mmHg, P < 0.001). Endothelial function was determined measuring the flow-mediated vasodilation (FMD) of the brachial artery. HRR by Iva increased FMD by 18.5% (Iva 7.3 ± 2.2% vs. placebo 6.0 ± 2.0%, P < 0.001). Aortic distensibility was characterized by MRI. HRR by Iva increased aortic distensibility by 33.3% (Iva 0.003 ± 0.001/mmHg vs. placebo 0.002 ± 0.010/mmHg, P < 0.01) and circumferential cyclic strain by 37.1% (Iva 0.062 ± 0.027 vs. placebo 0.039 ± 0.018, P < 0.0001). Conclusion: Heart rate reduction with Iva increased endothelium-dependent vasodilation and reduced arterial stiffness in patients with stable CAD. These findings corroborate and expand the results collected in experimental studies and indicate the importance of heart rate as a determinant of vascular function.